Exploring the Irish National Folklore Ethnography Database (Dúchas) for Open Data Research on Traditional Medicine Use in Post-Famine Ireland: An Early Example of Citizen Science - Koay, Aaron; Shannon, Fiona; Sasse, Astrid; Heinrich, Michael; Sheridan, Helen (Frontiers in Pharmacology, 2020)
A rich archive of oral and ethnological literature is housed in the National Folklore Collection, in University College Dublin, Ireland. The Schools’ Manuscript Collection is one body of information that contains a wealth of ethnographic material, including that of an ethnomedicinal nature, collected by schoolchildren across Ireland in the 1930s, in an early example of Citizen Science. The collection has been digitalised and is available online at Dúchas.ie. Furthermore, there is an on-going and related project, the Meitheal Dúchas.ie Community Transcription project that enables the database to be easily searched, and thus used for research purposes. This study analyses the user interface and functionality of the Dúchas database for ethnomedical research by utilising probes in the form of plants, within the collection, that have been previously identified as used for medicinal purposes. Limitations and biases associated with both the original collection of the material and the Dúchas database, that impact on the quality and utility of extractable data have been identified, and where possible specific procedures adopted to counteract such limitations. This study provides an insight into; the use of Dúchas.ie for ethnographic research, the use of plants for medicinal purposes in post famine Ireland and is the first tangible example of Citizen Science in ethnomedical research in Ireland.